Importance of specialized paediatric and neonatal transport. Current situation in Spain: Towards a more equitable and universal future - Nuria Millán García del Real; Laura Sánchez García; Yolanda Ballesteros Diez; Raquel Rodríguez Merlo; Alberto Salas Ballestín; Raquerl Jordán Lucas; Nieves de Lucas García (Elsevier, 2021)
Specialized paediatric and neonatal transport is a useful and essential resource in the interhospital transfer of these patients. It allows bringing the material and personal resources of an intensive care unit closer to the regional hospitals where the patient can be found. The benefits of these teams are very well demonstrated in the literature. These units should be part of the emergency systems, while it would be recommended that they be staff integrated in the tertiary hospitals, in order to maintain the necessary skills and competencies. The team, made up of physicians, nurses and emergency medical technicians, must master both the pathophysiology of transport and that of the critical patient in this age range. A high quality of both human and care is important, so continuous training and periodic recycling will be essential to be compliant with the quality indicators in transport. Likewise, it is essential to have specific vehicles adapted to this function, which allow carrying the wide variety of necessary material, as well as the electromedicine that is required. However, in Spain this paediatric and neonatal transport model is not standardized and therefore is not homogeneous: there are different models that do not always provide adequate quality, making it necessary to implement specialized units throughout the country to guarantee sanitary transport quality to any critical child or neonate. Resumen: El transporte pediátrico y neonatal especializado es un recurso útil y esencial en el traslado interhospitalario de estos pacientes. Permite acercar los recursos materiales y personales de una unidad de cuidados intensivos a los hospitales comarcales donde se pueda encontrar el paciente. Los beneficios de estos equipos están muy bien demostrados en la literatura. Estas unidades deberían formar parte de los sistemas de emergencias, al mismo tiempo que sería recomendable que fueran personal integrado en los hospitales terciarios, con el fin de mantener las habilidades y competencias necesarias. El equipo, compuesto por médicos, enfermeros y técnicos de emergencias sanitarias tiene que dominar tanto la fisiopatología del transporte como la del paciente crítico en este rango de edad. Es importante una alta calidad tanto humana como asistencial, por lo que la formación continuada y el reciclaje periódico serán imprescindibles para poder cumplir correctamente con los indicadores de calidad en transporte. Así mismo, es fundamental contar con vehículos propios y adaptados a su función, que permitan llevar la gran variedad de material necesario, así como la electromedicina que se requiere. Sin embargo, en España este modelo de transporte pediátrico y neonatal no está estandarizado y por lo tanto no es homogéneo: existen diferentes modelos que no siempre aportan una adecuada calidad, siendo necesario la implantación de unidades especializadas en todo el país para garantizar un transporte sanitario de calidad a cualquier niño o neonato crítico.